SURAT KETERANGAN TANAH ADAT (SKT-A) OLEH DAMANG KEPALA ADAT TERKAIT PEMBUATAN SERTIPIKAT TANAH DI PROVINSI KALIMANTAN TENGAH: Pendekatan Konsep Al- adah al- Muhakkamah - Setiawan, Ferry (Fakultas Syariah, 2017)
This journal aims to assess whether the Certificate of Indigenous Land created by Damang traditional leader can serve as a means of proof in land registration pursuant to Article 24 Paragraph (1) of Government Regulation No. 24 of 1997 on Land Registration and legal certainty for holders of the Certificate of Indigenous Land , This research is a normative legal research (Normative Legal Research) that use the approach legislation and conceptual approaches. Then assisted with legal materials will be described, described, and analyzed in relation to one another. In this study it was found that the Certificate of Indigenous Land created by Damang traditional leader based regulation Indigenous Institute Central Kalimantan can not be recognized as a means of proof in land registration as provided in Article 24 Paragraph (1) of Government Regulation No. 24 of 1997 on Land Registration. With the Certificate of Indigenous Lands can not be evidence in land registration, then it can not guarantee legal certainty for holders of indigenous land rights in Central Kalimantan.